1996
DOI: 10.1097/00005176-199602000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber in Weaning Cereals: A Study of the Effect on Stool Characteristics and Absorption of Energy, Nitrogen, and Minerals in Healthy Infants

Abstract: We evaluated the effect of increased dietary fiber (DF) content in weaning cereals based on wheat/soy (8.0 and 1.8% DF) and wheat/milk (5.3 and 2.0% DF) in healthy, formula-fed infants 7-17 weeks old. The study had a cross-over design, each infant acting as his or her own control. Stool characteristics and anthropometry were monitored over 4-week periods in groups of 34 (wheat/soy) and 23 (wheat/milk) infants. Absorption of zinc (Zn) and calcium (Ca) was studied by measuring the fecal excretion of stable isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Bioavailability from a soluble iron compound, ferrous sulfate, is usually used as a reference in studies in which bioavailability from different iron compounds is evaluated. Although no direct comparison with ferrous sulfate was included in the present study, the results of our previous study in healthy infants (19) indicated that iron bioavailability from ferrous sulfate added to a similar wheat and soy cereal was in the same range (< 0.9-9.1%; n = 6) as that from the test meals labeled with ferrous fumarate used in the present study. Iron bioavailability from iron fortification compounds depends not only on the characteristics of the compounds per se but also on the overall composition of the diet.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Bioavailability from a soluble iron compound, ferrous sulfate, is usually used as a reference in studies in which bioavailability from different iron compounds is evaluated. Although no direct comparison with ferrous sulfate was included in the present study, the results of our previous study in healthy infants (19) indicated that iron bioavailability from ferrous sulfate added to a similar wheat and soy cereal was in the same range (< 0.9-9.1%; n = 6) as that from the test meals labeled with ferrous fumarate used in the present study. Iron bioavailability from iron fortification compounds depends not only on the characteristics of the compounds per se but also on the overall composition of the diet.…”
Section: Discussionmentioning
confidence: 66%
“…The addition of ascorbic acid in that study was equivalent to a molar ratio of 2:1 relative to iron (22). However, the addition of approximately the same amount of ascorbic acid to infant cereals made from high-extraction rate wheat flour and soy flour (less refined), containing relatively high contents of phytic acid, resulted in lower iron bioavailability (19). Thus, the ability of ascorbic acid to overcome the inhibitory effect of phytic acid clearly depends both on the amount of phytic acid in the food and on the amount of ascorbic acid present (23).…”
Section: Discussionmentioning
confidence: 88%
“…The latter is affected by certain dietary components known to inhibit and enhance non‐haem iron absorption (Hallberg & Hulthén, 2000). Of the inhibitors, phytates found in rice and unrefined maize (Hallberg et al ., 1989; Sandberg et al ., 1989), the two major staples of complementary diets consumed in the Philippines, have a major inhibiting effect on non‐haem iron absorption in both adults (Hallberg et al ., 1989; Sandberg et al ., 1999; Hurrell et al ., 2002, 2003) and infants (Davidsson et al ., 1996). Further, their inhibitory effect is dose‐dependent (Hallberg & Hulthén, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are numerous studies investigating the effects of cereal, vegetable and fruit ®bres on the absorption of Ca in animals and humans. Most of them have reported no effect on Ca absorption or balance (Wisker et al, 1991;Davidsson et al, 1996). However, some studies described a decrease in Ca absorption with ingestion of dietary ®bres under certain conditions (Knox et al, 1991;O'brien et al, 1993).…”
Section: Discussionmentioning
confidence: 99%